Database «Uncensored Siberian periodicals (1920-1990)» - E. N. Savenko; N. A. Balytkina (Библиосфера, 2016)
The article discusses the problem of forming an electronic database of uncensored periodicals of the Siberian region. The modern state and prospects of applying information technologies to study samizdat are highlighted. Basic structural elements of the created information resource are shown. Possibilities of electronic database to represent the general picture of developing regional uncensored printing are characterized.